2000
DOI: 10.1002/(sici)1097-0231(20000331)14:6<496::aid-rcm899>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of missed cleavage sites, tryptophan oxidation and N-terminal pyroglutamylation after in-gel tryptic digestion

Abstract: Peptide mass fingerprinting is a powerful tool for the identification of proteins. Trypsin is the most widely used enzyme for this purpose. Therefore, 104 protein digests from human Jurkat T cells and Mycobacterium were analyzed considering missed cleavage sites, tryptophan oxidation and N-terminal pyroglutamylation. About 90% of the matched peptides with missed cleavage sites could be classified into three groups: (i) lysine and arginine with a neighbouring proline on the carboxy-terminal side, (ii) neighbori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
104
2
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 38 publications
8
104
2
2
Order By: Relevance
“…A possible explanation for this phenomenon is that TiO 2 used for enrichment not only enriches for phosphorylated residues, but also acidic residues, leading to an increased likelihood of enriching peptides that are phosphorylated and also contain more acidic residues. These phosphopeptides are thus more likely to have missed cleavage sites because of the increased likelihood of aspartic and glutamic acid residues occurring adjacent to a tryptic cleavage sites (14). We conclude that these missed cleavages are due to phosphorylation occurring in close proximity to sites of proteolytic cleavage and recommend that a higher number of missed cleavages events should be allowed during the database searching step of phosphoproteomics experiments.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…A possible explanation for this phenomenon is that TiO 2 used for enrichment not only enriches for phosphorylated residues, but also acidic residues, leading to an increased likelihood of enriching peptides that are phosphorylated and also contain more acidic residues. These phosphopeptides are thus more likely to have missed cleavage sites because of the increased likelihood of aspartic and glutamic acid residues occurring adjacent to a tryptic cleavage sites (14). We conclude that these missed cleavages are due to phosphorylation occurring in close proximity to sites of proteolytic cleavage and recommend that a higher number of missed cleavages events should be allowed during the database searching step of phosphoproteomics experiments.…”
Section: Resultsmentioning
confidence: 91%
“…One possible explanation is that the proximity of phosphorylated residues to arginine/lysine residues (12,13) or acidic residues such as aspartic and glutamic acid (14) can hamper the efficiency of digestion by trypsin. An analysis of our data showed that, for 42% of the tryptic phosphopeptides, a phosphorylated residue was 1 or 2 aa away from the cleavage site, suggesting that the phosphorylated residue might have hindered cleavage by trypsin as noted previously (12,13).…”
Section: Resultsmentioning
confidence: 99%
“…Although the characterization of the N-terminal status of the protein and especially NAA is the main goal of this study, the approach used here has been previously used for phosphopeptide enrichment and as mentioned earlier for the characterization of C terminus peptides and N terminus pyroglutamylated peptides (61). In depth investigation of the remaining unmatched spectra uncovered other co-and posttranslational modifications or numerous artifacts such as sodium and potassium peptide cationization (62).…”
Section: Resultsmentioning
confidence: 99%
“…Both CS and GM samples also contained peptide 896 -916 (2437.15 Da), in which Lys-C cleavage had occurred at Lys-916. The signal for 896 -916 was much less intense than that for 896 -918, presumably reflecting the fact that cleavage at Lys-916 was strongly inhibited by the flanking Glu residues (20). Furthermore, peptide 896 -916 is found in Pma2, a poorly expressed isoform of yeast plasma membrane H ϩ -ATPase (21), whereas peptide 896 -918 is unique to Pma1.…”
Section: Journal Of Biological Chemistry 35473mentioning
confidence: 99%